Teknis Pendirian Perbankan Syariah di Indonesia - Desfianti, Silvia; Nurnasrina, Nurnasrina; Syahfawi, Syahfawi (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
Syariah banking as an important component of banking law in Indonesia is currently experiencing rapid growth. The existence of Shariah banking is expected to help solve various problems in Indonesia, especially poverty. In the midst of its development, Shariah banking has not been able to handle the market share where the majority of the market share comes from people from the middle class. In addition, the education and socialization of Shariah banking is insufficient, so there is a diversity of public perceptions regarding Shariah banking. Pros and cons occur in society regarding the establishment of Sharia banks, where the benefits of Sharia banking are enormous, both in the economic world and in the future. This research uses literature review. Review using a qualitative approach. Primary data sources in this research were obtained from observations or research observations on problems that occur with Sharia banking management. Meanwhile, secondary data was obtained from good literature and books, journals and other sources related to current materials.